Pengembangan Media Pembelajaran Berbantuan Aurora 3d Presentation Pada Mata Pelajaran Administrasi Umum Kelas X OTP Di SMK Negeri 1 Jombang - Syehifan Praha Sadani; Brillian Rosy (Universitas Negeri Surabaya, 2021)
Aurora 3D Presentation is a software to create 3D presentation slides that can process slides by producing various images, text and video models in 3-dimensional form. Based on these, this study aims to (1) Describe the results of the development process of learning media, (2) Analyze and find out the feasibility of learning media and (3) Analyze student responses to Aurora 3D Presentation-assisted learning media in general administration subjects in class X OTP at SMK Negeri 1 Jombang. In this study, researchers used the 4D media development model. Where the 4D stage consists of define, design, develop, and disseminate. Based on the results of the validation of Aurora 3D Presentation media development on the validation of the material obtained results of 95.67% with